Q: X2 plus 3x plus 10 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 + 3x - 10 = (x + 5)(x - 2) ⇒ x = -5 or 2

x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}

3x-1 = 11 3x = 11+1 3x = 12 x = 4 Therefore: x2+2 = 18

-2x + 3x = -4 By combining like terms we get: x = -4.

x2 + 3x - 7 = 5x + 8; thus, x2 + 3x - 7 - 5x - 8 = x2 - 2x - 15 = (x - 5)(x + 3) = 0. Therefore the solution is x = 5 or -3.

Related questions

x2 + 3x - 10 = (x + 5)(x - 2) ⇒ x = -5 or 2

x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.

x = -5 x = 2

x = 2

x2 + 3x + 7 = 5 ∴ x2 + 3x + 2 = 0 ∴ (x + 1)(x + 2) = 0 ∴ x ∈ {-2, -1}

If you factor x2 - 3x - 10, you'll get (x-5) (x+2). If your equation is x2 - 3x -10 = 0, then x = 5, and x = -2.

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0

x2+3x-10 = (x+5)(x-2) when factored

3x-1 = 11 3x = 11+1 3x = 12 x = 4 Therefore: x2+2 = 18

-2x + 3x = -4 By combining like terms we get: x = -4.

x2 + 3x - 7 = 5x + 8; thus, x2 + 3x - 7 - 5x - 8 = x2 - 2x - 15 = (x - 5)(x + 3) = 0. Therefore the solution is x = 5 or -3.

x=-11